APPLICATION OF NEUROFEEDBACK TECHNOLOGIES IN INDIVIDUAL TEACHING: THEORETICAL BASIS AND PRACTICAL APPROACH (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article examines the theoretical foundations and practical aspects of applying neurofeedback technologies in the individualized learning process. Neurofeedback technology uses electroencephalography (EEG) to monitor brain bioelectrical activity in real time, providing feedback that teaches learners to regulate their cognitive states. The article covers the psychological-pedagogical foundations of individualized instruction, the neurofeedback mechanism, international meta-analyses, and implementation possibilities in Uzbekistan schools.